User consultation and the design of healing architecture in a cardiology department – ways to improve care for and well-being of patients and their relatives - Maja Forum Riisbøl; Connie Timmermann (Nordic Journal of Arts, Culture and Health)
Purpose: To explore, from the perspectives of patients, relatives and nurses, how an observation room in a Department of Cardiology can be redecorated and redesigned to improve the care for and well-being of patients and their relatives. Background: Patients in modern hospitals are to a large extent met by clinical sensory impressions, such as medical and technical equipment, colourlessness, and randomly designed and furnished surroundings. Sensory impressions from such hospital surroundings are shown to be associated with unfamiliarity, which promote a negative mood and increase feelings of insecurity and vulnerability during hospitalization. It is therefore important to recognize that today’s hospital environment may be interfering with quality of care and experiences of well-being. Design: A mixed-method approach was used, based on user consultation, in order to inform the redecoration and redesign of the observation room. Data were collected through a combination of questionnaires and participant observations, including informal conversations with a total of 12 participants, including nurses, patients and relatives. Questionnaires were answered by a total of 58 patients and relatives. Findings: The hospital environment, only sparsely decorated and very randomly designed, was found to negatively influence both the care provided and experiences of well-being. Three themes were identified as important when redecorating and redesigning the observation room: (i) The ambience of the room, including music, wall decorations and colours, (ii) The presence of nature and (iii) Privacy. Conclusion: The patients and relatives perceive the surroundings in the observation room as significant to their well-being. Nurses identify the sensory impressions in the environment as a significant component in the care offered to the patients and their relatives. Value: This study describes how a user consultation process can be initiated and offers a valuable contribution to how hospital environments can be redecorated and redesigned to support well-being.